Honesty in Human Subject Research. - Um, Sungwoo (Journal of Bioethical Inquiry, 2025)
In this paper, I discuss the ethical issues related to deception in human subject research in terms of honesty. First, I introduce the background and suggest the conception of honesty that understands it as involving respect for the right not to be deceived (RND). Next, I examine several ways to address the ethical issues of deceptive elements in the human subject research and show why they fail to adequately meet the demand of honesty. I focus on how to make an honest research plan and examine after participation and before participation phases in turn. Then I conclude by suggesting possible strategies to minimize dishonesty in human subject research.